Influence of Rb doping in optical and thermoelectric properties of KCl – A DFT approach. (2022) - Manjula, M.; Krishnaveni, S.; Viswanathan, E.; Muthumari, M.
Abstract: The ground-state structural, electronic, optical and thermoelectric properties of the K0.5 Rb0.5 Cl alloy have been studied by using the full potential linearized augmented plane wave (FP-LAPW) scheme based on the density functional theory in the frame of generalized gradient approximation (GGA). In order to model K1-x Rbx Cl alloy, 16-atoms supercell of the type 2 × 2 × 2 is employed. The lattice structure of K0.5 Rb0.5 Cl alloy is obtained by replacing four K atoms by Rb atoms in the crystal lattice of KCl. The band structure and density of states histograms are plotted and discussed. The valence band maxima (VBM) and the conduction band minima (CBM) of parent KCl and K0.5 Rb0.5 Cl is located at Г point, resulting in a direct band gap. The calculated results are found to be in good agreement with available theoretical and experimental data. The optical properties are calculated for radiation up to 13.5 eV. The important peaks of the optical spectra calculated in terms of electronic structure. From the optical spectra, optics technology and the useful optoelectronic is predicted.